Educational Da'wah Strategy for Increasing Religious Activities - Pratama, Arizqi Ihsan; Rusman, Deni; Zahir, Mustofa (Atthulab: Islamic Religion Teaching and Learning Journal, 2022)
Da'wah is an activity to invite and call to goodness. All Muslims are obliged to carry out this virtue. SMP Darunnajah 2 Cipining as a formal educational institution for Junior High School provides a fairly good and interesting example to study. Da'wah is meant here is Da'wah to provide education and invitations to students to carry out and improve Worship to Allah SWT, do good deeds and read the Al-Quran. The method used is descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation. The results of the study indicate that the Educational Da'wah Strategy at SMP Darunnajah 2 Cipining is to carry out the following activities: Religious Tausiyah, Joint tahajjud, Perkajum (Thursday-Friday Camp), Safari Da'wah, filling out amaliyah worship books, Guidance on learning to read the Al-Quran. With these activities, students are encouraged to be more enthusiastic in worship and learning to read the Qur'an, and to be more polite in behavior. Dakwah adalah kegiatan mengajak dan menyeru kepada kebaikan. Semua umat Islam berkewajiban untuk menjalankan keutamaan ini. SMP Darunnajah 2 Cipining sebagai lembaga formal pendidikan Sekolah Menengah Pertama memberikan contoh kegiatan dakwah Pendidikan yang cukup baik dan menarik untuk dipelajari. Dakwah yang dimaksud disini adalah Dakwah untuk memberikan Edukasi dan ajakan kepada para siswa untuk menjalankan dan meningkatkan Ibadah kepada Allah Swt., beramal saleh dan membaca Al-Qur’an. Metode yang digunakan ialah metode deskriptif kualitatif. Hasil penelitian menujukan bahwa Strateri Dakwah Pendidikan di SMP Darunnajah 2 Cipining adalah dengan melakukan kegiatan sebagai berikut: Tausiyah Agama, tahajud Bersama, Perkajum (Perkemahan Kamis-Jumat), Safari Dakwah, pengisian buku ibadah amaliyah, Bimbingan belajar membaca Al-Quran. Dengan adanya kegiatan-kegiatan tersebut menjadikan para siswa terdorong untuk lebih semangat dalam beribadah dan belajar membaca Al-Qur’an, dan lebih sopan dalam berprilaku.